2022
DOI: 10.1093/plphys/kiac240
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of hydraulic thresholds across roots, stems, and leaves of two co-occurring mangrove species

Abstract: Mangroves are frequently inundated with saline water and have evolved different anatomical and physiological mechanisms to filter and, in some species, excrete excess salt from the water they take up. Because salts impose osmotic stress, interspecific differences in salt tolerance and salt management strategy may influence physiological responses to drought throughout the entire plant hydraulic pathway, from roots to leaves. Here, we characterized embolism vulnerability simultaneously in leaves, stems, and roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 94 publications
1
5
0
Order By: Relevance
“…(2018), and thus faster stomatal closure for mangroves. Furthermore, mangroves for the adaptation of high salinity of intertidal habitats have evolved a series of water-protection traits, such as highly embolism-resistant xylem (Jiang et al ., 2017; Jiang et al ., 2021; Jiang et al ., 2022), high hydraulic-capacity in leaf and root tissues (Aritsara et al ., 2022), and extreme osmotic adjustment (Reef & Lovelock, 2015). They therefore may have enhanced stomatal regulation with a highly sensitive stomatal response to VPD suited to this adaptation to water-deficit prone habitats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2018), and thus faster stomatal closure for mangroves. Furthermore, mangroves for the adaptation of high salinity of intertidal habitats have evolved a series of water-protection traits, such as highly embolism-resistant xylem (Jiang et al ., 2017; Jiang et al ., 2021; Jiang et al ., 2022), high hydraulic-capacity in leaf and root tissues (Aritsara et al ., 2022), and extreme osmotic adjustment (Reef & Lovelock, 2015). They therefore may have enhanced stomatal regulation with a highly sensitive stomatal response to VPD suited to this adaptation to water-deficit prone habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Mangrove plants live in intertidal coastal zones of the tropics and subtropics (Duke et al ., 1998), an environment that is associated with high salt concentration and hypoxia in the soil rhizosphere as well as high atmospheric evaporative demand (Reef & Lovelock, 2015). To adapt to such habitats, mangroves have developed efficient regulation of water consumption, high resistance to xylem embolism, high tolerance to desiccation and high leaf capacitance (Reef & Lovelock, 2015; Jiang et al ., 2017; Jiang et al ., 2021; Jiang et al ., 2022; Aritsara et al ., 2022). Mangroves have longer guard cell length for a given stomatal density than other vascular plants (Agduma et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Initial water potentials were checked and always close to -0.1 MPa. Pressure–volume curves were constructed for each sample by repeatedly measuring the bulk water potential using a pressure chamber (0.01 MPa resolution; PMS Instruments, Albany, OR, USA) and the mass to determine the relationship between water potential and water content following standard methods ( Scholander et al., 1965 ; Tyree and Hammel, 1972 ; Sack and Pasquet-Kok, 2011 ; Roddy et al., 2019 ; Jiang et al., 2022 ). Prior to each water potential measurement, samples were enclosed in humidified plastic bags for about 20 min to allow equilibration.…”
Section: Methodsmentioning
confidence: 99%
“…Plant species with low water transport capacity may also exhibit reduced gas exchange through their stomata because water loss from the leaves is likely also limited by stems' hydraulic supply and hydraulic architecture (Brodribb & Feild, 2000, Santiago et al, 2004). Thus, the structure and water transport properties of the vascular system affect the balance between water supply and total transpiring leaf area (Cardoso et al, 2020, Jiang et al, 2022, Sorek et al, 2021). Previous studies have suggested that a larger interconduit pit aperture diameter may confer higher rates of mass‐based photosynthesis in conifers (Song, Sterck, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%